Philanthropic Behaviour: Intention of University Teknologi MARA Alumni to Contribute to the Higher Education Institution Waqf Fund - Ahmad, Mohammad Firdaus; Samsudin, Khairul Jannah; Ismail, Zanita (Research and Innovation in Technical and Vocational Education and Training, 2023)
As Muslims, we believe that good deeds and contributions will be rewarded in the hereafter. The population for this study is university alumni who have graduated since the establishment of the university. The total number of alumni in 2015 was 645,862. As the number of the population is too large, the researcher can’t do all of them. Hence, a smaller number of respondents is needed through the sampling technique. The method used under PLS-SEM software comprises PLS Algorithm, Bootstrapping and Blindfolding. These methods are to be appropriate for testing the hypotheses that answer the objectives of the study. The method made it suitable to find out the profiles of donors and non-donors among the university alumni. Furthermore, the SPSS software was chosen to interpret the data as PLS-SEM software did not support this type of data analysis. This study also shows that most of the alumni have the proper knowledge that one Muslim should possess about waqf. However, even though the alumni have the capability and proper knowledge about waqf, it did not encourage them to contribute to the fund. Hence, the alumni also had the perception that people who are close to them do not agree that they should help people in need financially. As a conclusion, this study was able to study the philanthropic behaviour of UiTM alumni in contributing to the UiTM education waqf fund.